See her die - Leigh, Melinda (Seattle, WA : Montlake, 2020)
"New sheriff Bree Taggert is called to a shooting in a campground shuttered for the winter. But she arrives to find a perplexing crime. There is no shooter, no victim, and no blood. No one but Bree believes the sole witness, Alyssa, a homeless teenager who insists she saw her friend shot. Bree calls in former deputy Matt Flynn and his K-9 to track the killer and search for Alyssa's friend. They discover the battered corpse of a missing university student under the ice in Grey Lake - but it's not the victim they were looking for. When two more students go missing and additional bodies turn up, Bree must find the link between the victims. She knows only one thing for certain: the murders are fueled by rage. When Alyssa disappears, Bree must race against time to find her before her witness becomes another victim."--Publisher description.
108489
Keywords: Murder -- Investigation -- Fiction; Missing persons; Sheriffs; Serial murderers; Police dogs; Detective and mystery stories; Thrillers (Fiction); Suspense fiction